Partisipasi Masyarakat Dalam Pengelolaan Sampah Di Kelurahan Palattae Kecamatan Kahu Kabupaten Bone - Jumarni, Jumarni; Nasrulhaq, Nasrulhaq; Fatmawati, Fatmawati (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2021)
This study purposed to determine how the form of community participation in waste management and how the level of community participation in waste management in the Palattae sub-district, Kahu District, Bone Regency .  This study used  qualitative with the type of phenomenological research that emphasized the subjectivity of human life experiences. The number of informants in this study was 11 people. Data collection techniques were observation, interviews and documentation. Data analysis used interactive analysis models. The results showed that community participation in waste management in Palattae sub-district, Kahu District, Bone Regency. it must be considered what was an indicator of community participation, namely the existence of donations, thoughts, material contributions and donations of energy and donations These four indicators run well and could be seen from the community participation in the Village Office that continued to participate Community participation in the form of thoughts actually it had been going well because there were people who often carried out community service. Although some people only carried about these activities.